Urgensi Kepemimpinan Transformatif Bagi Perpustakaan Perguruan Tinggi - Sari, Kristina (Pustakaloka, 2015)
TheÂ  globalizationÂ  eraÂ  hasÂ  givenÂ  aÂ  consequenceÂ  of massive changesÂ  inÂ  peopleâsÂ  lifeÂ  includingÂ  theÂ  universityÂ  organization.Â  The increasing of information technology and the rapid fow of information makeÂ  theÂ  universityÂ  libraryÂ  asÂ  anÂ  informationÂ  centerÂ  andÂ  knowledge undergoesÂ  variousÂ  changesÂ  inÂ  theÂ  roleÂ  andÂ  functions.Â  AtÂ  such circumstances, the role of the leadership of the university library should have a clear vision for the challenges that occur. The quality of a leader in the process of ongoing changes should have a future-oriented. Libraries as a nonproft organization cannot avoid the changes, the presence of the development of information technology is a major external impact will changeÂ  theÂ  elementsÂ  ofÂ  theÂ  organizationâsÂ  library. EachÂ  organization hasÂ  diferentÂ  targetsÂ  to meetÂ  theÂ  needsÂ  andÂ  theÂ  dominantÂ  factorÂ  that encourage the changes.